Digital convergence propitious convergence between industries: main companies are involved in the capital market and concentrate higher revenues in 2013 - Gutiérrez-Rentería, María Elena (2022)
The digital convergence has led to a change in the business model of some companies in the telecommunications and media industry. This research presents empirical evidence related to the existence of a concentration in the market structure with respect to the income of certain firms. These organizations take part of the thirteen industries that converge globally. The study reflected the analysis of all related firms participating into digital markets. These firms also are registered in capital markets and are listed in the database of 2000 big firms from the Forbes Magazine in 2013.